Meningkatkan Keterlibatan Orang Muda Katolik dalam Liturgia di Stasi Santo Petrus P. Nauli Selayang Paroki Maria Bunda Pertolongan Abadi Binjai - Natalia Suarni Sijabat; Tri Chandra Fajariyanto (CV. ALIM'SPUBLISHING, 2026)
Catholic Youth (OMK) is an integral part of the Church that has a strategic role in supporting the sustainability of Church life and ministry. OMK involvement in the liturgy is one form of real participation in realizing the calling as members of the Church. However, based on the phenomenon found at the St. Petrus Pardomuan Nauli Selayang Station, Mary Mother of Eternal Help Parish, Binjai, OMK involvement in liturgical services is still relatively low. This study aims to describe the involvement of Catholic Youth in the liturgy and identify efforts that can be made to increase this involvement. This study uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation techniques involving OMK mentors, station administrators, and OMK members as research informants. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, while the validity of the data was tested using source triangulation and technical triangulation. The results of the study are expected to provide an overview of the forms of involvement of OMK in liturgical services as lectors, psalmists, and conductors, as well as reveal efforts to increase involvement through catechesis, strengthening friendships, faith accompaniment, and ongoing development.